Moral distress from human to veterinary medicine: a comparative analysis - De Mori, Barbara (Medicina e Morale, 2019)
Studies on professional hardship in the healthcare professions are constantly growing. These studies have identified various ethical discomforts, such as moral distress, whose diagnosis and treatment is of critical importance. However, in the field of animal care professions, such as that of the veterinary surgeon, these studies have rarely been studied in depth, with serious repercussions on professional practice. In general, society struggles to understand how difficult it is for those who work with animals to manage the ethical conflicts that arise between the needs of the profession, the needs of the animals and the demands of those who are owners or proxies for the animal. Moral distress has only recently been recognized in veterinary medicine and is provoked, as in the field of human medicine, by the inability to find an agreement between one's vocation and the moral tensions that the exercise of the profession brings every day. In this contribution, through a comparison with the studies carried out in the field of healthcare professions in human medicine, moral distress is explored in the context of the veterinary medical profession, focusing attention on the specific ethical issues that are involved in the triadic relationship between surgeon, animal patient and owner.